Effect of 38%hydrogen peroxide agent on color change of composite resins stained with tea and coffee beverages (An in vitro study) (Mustansiria Dental Journal, 2018)
Background: The esthetic application of bleaching materials has gained popularity,with consequences for teeth and restorative materials. The purpose of this an invitro study was to investigate the effect of in-office bleaching agent (38%hydrogen peroxide) on the color change of three composite resins after stainingwith tea and coffee beverages.Materials and Methods: Sixty disc-shaped samples from three different compositeresins (Tetric Ceram, Tetric Flow and Tetric Evo Ceram) were used in this study.The samples of each group were randomly divided into two subgroups accordingto type of beverages (tea and coffee) used for staining of samples. After stainingof composite resins the total color change (ΔE1 ) was calculated usingspectrophotometer, then the samples immersed in WHITEsmile® office bleachingagent for 15 min x 3 times with a 7 days interval followed by ΔE2 calculation.Data were subjected to the ANOVA, LSD and student t-test at 0.05 significancelevel.Results: The results revealed that, there was clinically significant color change ΔE>3.3 with a statistically highly significant differences (P=0.000) for all the groups.Coffee causes more discoloration than tea. After bleaching, the samples becamewhiter in color and only appreciable by skillful operator but considered clinicallyacceptable ΔE1 - ΔE2 < 3.3.Conclusion: Tea and coffee beverages causes discoloration in composite but thiseffect was depended on the type of beverages and composite resins. The most ofcolor change occurred with Tetric Flow composite resin after immersion in coffeebeverage. The bleaching agent (38% hydrogen peroxide) can remove the stainingof composite resins and make its color clinically acceptable.